European Definitions, Current Use, and EMA Stance of Platelet-Rich Plasma in Sports Medicine - Fiorentino, Stefano; Roffi, Alice; Filardo, Giuseppe; Marcacci, Maurilio; Kon, Elizaveta (The Journal of Knee Surgery, 2015)
Platelet-rich plasma has been the focus of much attention over the last few years as an appealing biological approach to favor the healing of tissues otherwise doomed by a low healing potential. In Europe, the regulatory framework concerning the blood system is currently disciplined by Directive 2002/98/EC of the European Parliament and Council of January 27, 2003, which sets out quality and safety rules for collecting, controlling, processing, preserving, and distributing human blood and its components, acknowledged in the various States of the Union with internal regulations. This lack of homogeneity in the European legal landscape will probably lead the Community legislature to intervene in the near future, to even out the “rules of engagement” of this peculiar class of biomaterials.
Keywords: PRP; European regulation; European definitions; sports medicine